Direct Nature Experiences On Biodiversity Knowledge, Attitudes And Conservation Willingness Among Maldivian Children - Abdulla, Faruhana (2023)
Historically abundant DNEs in children’s everyday lives formed the roots of sustainable practices in the Maldives. Although contemporary Maldivian children may be subject to a loss of DNEs, the extent of this problem or its consequences remain largely unknown. This study aimed primarily to establish and understand current trends in DNEs and their influences on biodiversity knowledge (BK), attitudes towards biodiversity (AA), and conservation willingness (CW) among 11–12-year-old school children in the Maldives in different island environments. It also aimed to explore and understand the contextual factors that influence these experiences. This study employed an embedded mixed-method design composed of an online survey (n=429) and focus group interviews (n=34) from schools in seven islands. The quantitative data were analyzed using descriptive and inferential statistics. Results demonstrated higher DNE frequentness (EF) and Seen-Alive-Only (SAO) experience levels for most children outside the Male’ area, while the variety of experiences (VNEs) was similar in all IEs. Several species were not seen by many children regardless of IE. Most children demonstrated a low level of BK and moderate or low levels of AA and CW. One-way ANOVA tests showed that only BK and AA increased significantly with increased EF. VNE and SAO showed significant positive correlations with BK and AA, but only VNE is significantly correlated with CW.